Metal nanoparticles on graphene based materials used as catalysts for alcohol electro-oxidation - Wang, Haibo (2015)
The research work presented in this thesis is mainly to develop metal nanoparticles (NPs) on graphene based support and apply these composites as catalysts for the methanol and glycerol electro-oxidation. The purpose is to promote the activity and selectivity of catalysts in alcohol electro-oxidation by tuning properties of graphene based supports. Firstly, we obtained various water-soluble polymer functionalized graphene in dimethyl sulfoxide under ultrasonication. The atomic force microscope analysis and control experiment showed that polymer possessing the stronger interaction with graphene surface produced graphene with a thinner layer. Such polymer/graphene exhibited high conductivity and tunable surface property. As a result, a catalyst based on polyvinyl pyrrolidone (PVP)/graphene showed better methanol oxidation performance than that based on PVP/ reduced graphene oxide. By changing to another polymer, poly (4-vinylpyridine)/graphene showed stable and reversible response to pH, demonstrating its potential for sensor application. Secondly, Au NPs supported on various supports with different metal support interaction were synthesized and tested for glycerol electro-oxidation. Through off-line HPLC analysis, it was found that Au NPs supported on extended poly(4-vinylpyridine) functionalized graphene (Au-P4P/G) showed a much higher activity and better selectivity for three carbon products than those on carbon black, P4P functionalized reduced graphene oxide (Au-P4P/rGO) and poly(m-aminophenol) (PmAP) wrapped graphene (Au-PmAP/G). Based on XPS results, we proposed that lower d-band center in Au nanoparticles could change their adsorption ability for oxygen-containing groups, which might induce higher three carbon selectivity in glycerol electro-oxidation. Thirdly, a hybrid support consisting of nitrogen doped graphitic carbon and graphene (CNx/G) was prepared by annealing polypyrrole/GO at 800 oC. Pd NPs were then loaded onto the support by a microwave-polyol method. Pd-CNx/G was used as a catalyst for glycerol electro-oxidation. Through the comparison with Pd NPs on carbon black (CB), it was revealed that Pd NPs on support which containing nitrogen atoms could promote selectivity towards three carbon products as well as increase activity. Moreover, CNx/G showed higher surface area than CNx annealed from wire structured polypyrrole. It caused smaller size of Pd NPs on CNx/G and further increased its selectivity towards three carbon products.